2011
DOI: 10.1007/s12034-011-0115-3
|View full text |Cite
|
Sign up to set email alerts
|

Visible light photocatalytic properties of novel molybdenum treated carbon nanotube/titania composites

Abstract: Two types of molybdenum-carbon nanotubes and molybdenum treated carbon nanotubes/titania composites were prepared using a sol-gel method. These composites were characterized comprehensively by the BrauerEmett-Teller (BET) surface area, scanning electron microscopy (SEM), energy dispersive X-ray (EDX) analysis, X-ray diffraction (XRD), transmission electron microscopy (TEM) and UV-vis absorption spectroscopy. It was found that the photocatalytic degradation of a methylene blue solution could be attributed to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Researchers hope to find some non-noble metals to replace novel metals [56][57][58]. Zhang et al [59] reported the synthesis of Mo-decorated TiO2/CNTs (Mo-CT) composites. In this system, three parts Although many achievements have confirmed that the employment of 0D carbon materials as co-catalysts can actually enhance the photocatalytic performance of semiconductor photocatalysts, these materials are difficult to homogeneously disperse on the surface of main photocatalysts.…”
Section: D/0dmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers hope to find some non-noble metals to replace novel metals [56][57][58]. Zhang et al [59] reported the synthesis of Mo-decorated TiO2/CNTs (Mo-CT) composites. In this system, three parts Although many achievements have confirmed that the employment of 0D carbon materials as co-catalysts can actually enhance the photocatalytic performance of semiconductor photocatalysts, these materials are difficult to homogeneously disperse on the surface of main photocatalysts.…”
Section: D/0dmentioning
confidence: 99%
“…Researchers hope to find some non-noble metals to replace novel metals [56][57][58]. Zhang et al [59] reported the synthesis of Mo-decorated TiO 2 /CNTs (Mo-CT) composites. In this system, three parts play their own duty, respectively, and the interaction between them dramatically enhances the photocatalytic activity.…”
Section: D/0dmentioning
confidence: 99%